Water- and frost-resistance of crushed stone mastic asphalt concrete prepared on sevilen-modified bitumen - V. V. Yadykina; S. N. Navolokina; A. M. Gridchin (Вестник СибАДИ, 2022)
Introduction. Currently, increasing the durability of road asphalt concrete pavements is one of the urgent issues, the solution of which provides a significant economic effect achieved by increasing the turnaround time, as well as the overall service life of highways. Asphalt concrete pavements with prolonged wetting due to weakening of structural bonds can be destroyed due to crumbling of mineral grains, which leads to increased wear of the pavement and the formation of potholes. Water penetrates into micro defects in the structure of asphalt concrete, leading to a decrease in the strength of the material. As a result, the corrosion resistance of asphalt concrete is reduced. To improve the quality of the binder and the durability of the asphalt concrete pavement, in particular from crushed stone-mastic asphalt concrete (SMA), various modifying additives, including polymer ones, are used. In this regard, a promising direction is the use of polymers containing active groups, which are able to provide an increase in adhesion to mineral materials, including those from acid rocks, and, consequently, water resistance. One of these is the ethylene vinyl acetate copolymer (EVAC).Materials and methods. In order to study the effect of sevilen on the water and frost resistance of asphalt concrete mixtures, crushed stone-mastic asphalt concrete mixtures were prepared based on bitumen modified with БНД 70/100 sevilen made in the Moscow Oil Refinery Plant was used as the initial bitumen in the preparation of modified binders. Tests of crushed stone-mastic asphalt concrete mixtures were carried out for the indicator of the content of air voids in accordance with GOST R 58406.8.2019, the coefficient of water resistance in accordance with GOST R 58401.18-2019 and frost resistance in accordance with GOST 12801-98.Results. It has been established that the content of air voids in asphalt concrete samples significantly decreases with an increase in the concentration of sevilene, which will further contribute to a higher frost resistance of the road surface. It is shown that the use of sevilen with 22% vinyl acetate makes it possible to increase the coefficient of water resistance of asphalt concrete mixtures due to the presence of polar molecules in the composition of ethylene vinyl acetate, actively interacting with the mineral components of the asphalt concrete mixture. The use of sevilen improves the frost resistance of asphalt concrete samples. So, the smallest decrease in strength in tests for frost resistance was shown by samples with 5% sevilene. It was found that polymer asphalt concrete based on binder with sevilene containing 22% vinyl acetate, which corresponds to the maximum basicity of the polymer, has the highest resistance to humidity and temperature effects of the environment.